Relationship Level of Education, Work Period, and Knowledge of Nurses With Implementation of Discharge Planning at X Hospital South Jakarta - Triarti Astuti; Stefanus Andang Ides; Ni Luh Widani (MBUnivPress, 2024)
study aims to analyze the relationship between education, years of service, and knowledge of nurses with the implementation of discharge planning in the Inpatient Room of Hospital X. The research method used is a quantitative method with an analytical approach and a cross-sectional study design. Respondents in this study were nurses working in the Inpatient Room of X Hospital. Data were collected through questionnaires and analyzed using descriptive statistical techniques and regression analysis. The results showed that there was a positive relationship between nurse education (D3 Nursing), years of service (1-5 years), and knowledge of nurses with the implementation of discharge planning. This shows that nurses with D3 Nursing education have a better understanding regarding discharge planning, as well as nurses who have had 1-5 years of work experience. This research provides important implications for nursing management at X Hospital to improve the discharge planning process through a better understanding of the role of nurses in this process. In addition, nursing education institutions can also consider the results of this study as teaching materials that support curriculum development.